2012
DOI: 10.1038/mp.2012.104
|View full text |Cite
|
Sign up to set email alerts
|

Cis-acting regulation of brain-specific ANK3 gene expression by a genetic variant associated with bipolar disorder

Abstract: Several genome-wide association studies (GWAS) for bipolar disorder (BD) have found a strong association of the Ankyrin3 (ANK3) gene. This association spans numerous linked single nucleotide polymorphisms (SNPs) in a ~250 kb genomic region overlapping ANK3. The associated region encompasses predicted regulatory elements as well as two of six validated alternative first exons, which encode distinct protein domains at the N-terminus of the protein also known as ankyrin-G (AnkG). Using RNA Ligase-Mediated Rapid A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 35 publications
(48 reference statements)
4
68
0
1
Order By: Relevance
“…Since the 2 SNPs are in strong linkage disequilibrium (d' = 0.95), results are only presented for rs1938526 given evidence of an effect of this SNP on gene expression. 19 Analyses on the effects of rs10994336 on neurocognition (not shown) yielded similar but slightly less significant results. Table 2 and Table S1 in the Appendix, available at cma.ca/jpn, indicate the clinical and demographic characteristics of participants included in both the cognitive and imaging portions of the study.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Since the 2 SNPs are in strong linkage disequilibrium (d' = 0.95), results are only presented for rs1938526 given evidence of an effect of this SNP on gene expression. 19 Analyses on the effects of rs10994336 on neurocognition (not shown) yielded similar but slightly less significant results. Table 2 and Table S1 in the Appendix, available at cma.ca/jpn, indicate the clinical and demographic characteristics of participants included in both the cognitive and imaging portions of the study.…”
Section: Resultsmentioning
confidence: 70%
“…16,18 The risk-associated ANK3 SNPs are intronic, and rs1938526 and other SNPs have been associated with reduced gene expression. 16,19 Several studies have examined the role of these genetic variants on neurocognition. A study on BD found significant association between rs10994336 and sustained attention, but no effect on general intelligence, memory or executive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were not powered to detect sex differences or sex × gene interactions. The human variation in ANK3 may also change splicing or regional brain expression in ways not modeled in the current study (7,11,13,14,53).…”
Section: Discussionmentioning
confidence: 99%
“…The 190-kDa isoform is present at dendritic spines (11,12). Many of the risk alleles for ANK3 are in the five-prime upstream region, suggestive of changes of expression (13,14). Ankyrin-G protein expression was reduced in pyramidal AISs in superficial layers of schizophrenia cortex (15).…”
mentioning
confidence: 99%
“…ANK3 Alternative N Termini Differentially Regulate KCNQ2/3 and Na v Channel Association with AnkG-ANK3 has at least three alternative promoters and corresponding first exons encoding non-ankyrin N termini variants (namely exon1a, exon1e, and exon1b, encoding NT1-3, respectively; Fig. 9, A and B) (6,42,45,46). These promoters and alternative N termini exhibit tissue-and cell type-specific expression.…”
Section: Anti-gfp: Input Anti-gfp: Input Anti-gfp: Input N -R 7 H 1 Smentioning
confidence: 99%